The Use of Service Dogs for People With Physical Disabilities in Japan in Accordance With the Act on Assistance Dogs for Physically Disabled Persons - Takayanagi, Tomoko; Yamamoto, Mariko (Frontiers in Veterinary Science, 2019)
Japan learnt how to promote assistance dogs effectively by deliberating the issues and challenges that surrounded assistance dogs in the USA and Europe and the Act on Assistance Dogs for Physically Disabled Persons was issued in 2002. The aim of this paper is to provide information that may be useful for countries and areas that are seeking ways to regulate assistance dogs, especially in the context of the global problem in which dogs are falsely claimed to assist their partners. First, there is a description of the process through which Japan, where pet dogs have not been accepted in society, established the Act, which overcame the shortcomings of the previous situation. Second, it is shown the ways in which people living with assistance dogs have gained the right to have their dogs accompany them in public. Third, the current challenges faced by people with assistance dogs are documented. Finally, pictures of an example of an assistance dog certificate and of an assistance dog sign reveal how far the regulation of assistance dogs is achieved in Japan.